COX-2 expression in ampullary carcinoma: correlation with angiogenesis process and clinicopathological variables. Issue 5 (17th February 2006) - Perrone, G; Santini, D; Verzì, A; Vincenzi, B; Borzomati, D; Vecchio, F; Coppola, R; Antinori, A; Magistrelli, P; Tonini, G; Rabitti, C
Abstract : Background: There is evidence that the anti-neoplastic effect of non-steroidal anti-inflammatory drugs is attributable to cyclooxygenase-2 (COX-2) inhibition, but the exact mechanisms whereby COX-2 can promote tumour cell growth remain unclear. One hypothesis is the stimulation of tumour angiogenesis by the products of COX-2 activity. To data, there have been few clinicopathological studies on COX-2 expression in human ampullary carcinoma and no data have been reported about its relation with tumour angiogenesis. Objective: To investigate by immunohistochemistry the expression of COX-2 and the angiogenesis process in a series of primary untreated ampullary carcinomas. Methods: Tissue samples from 40 archival ampullary carcinomas were analysed for COX-2, vascular endothelial growth factor (VEGF), and an endothelial cell marker von Willebrand factor (vWF) by immunohistochemistry, using specific antibodies. Results: COX-2 expression was detected in 39 tissue samples (97.5%), of which two (5%) were graded as weak, 26 (65%) as moderate, and 11 (27.5%) as strong. Only one lesion (2.5%) was negative for COX-2 expression. VEGF expression was detected in 36 tissue samples (90%). A significant positive correlation was found between COX-2 and VEGF expression. No statistic correlation was found between COX-2 expression and microvessel density. Conclusions: COX-2 is highly expressed in ampullary carcinomas. This suggests an involvement of the COX-2 pathway in ampullary tumour associated angiogenesis, providing a rationale for targeting COX-2 in the treatment of ampullary cancer.